Aqueous Dispersions of Esterified Lignin Particles for Hydrophobic Coatings - Hua, Qi; Liu, Li-Yang; Karaaslan, Muzaffer A; Renneckar, Scott (Frontiers in Chemistry, 2019)
An aqueous biopolymer dispersion coating system was synthesized utilizing softwood kraft lignin and a long chain organic acid. The chemical treatment of lignin was a two-step procedure, which first consisted of hydroxyethylation of the phenolic groups on lignin utilizing ethylene carbonate and an alkaline catalyst. This first step resulted in the lignin containing more than 80% aliphatic hydroxyl functionality (1H NMR). Following this step, oleic acid was reacted with hydoxyethyl lignin in order to form ester derivatives. With nearly a total reduction in absorbance in the hydroxyl stretching region, FT-IR analysis showed the majority of the hydroxyl groups was esterified forming an ethyl oleate derivative. Semi-quantitative 13C NMR analysis of the lignin revealed 88% substitution of the lignin hydroxyl groups. This derivative was soluble in organic solvent such as toluene and tetrahydrofuran. Solutions of lignin derivatives were slowly precipitated through dialysis, resulting in a stable dispersion of lignin microparticles in distilled water. The 1–2 μm average diameter size of the precipitated particles was found with dynamic light scattering of the suspensions. Spray and spin coating were used to apply the lignin derivative dispersion to different surfaces. For both coating methods, the lignin-based particles enhanced the hydrophobicity of all the substrates tested, resulting in increased water contact angles for glass, kraft pulp sheets and solid wood. Benign reagents involved in the coating synthesis utilized natural compounds that are known to repel water in nature. Combined with the avoidance of volatile organic solvents during application, this process provided a low environmental footprint solution for synthesis of hydrophobic coatings.